New Geographies of Language Language, Culture and Politics in Wales - Jones, Rhys.; Lewis, Huw.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2019)
This book develops a novel approach to the study of language, bringing it into dialogue with the latest geographical concepts and concerns and provides a comprehensive account of the geography of Welsh language analysing policy development, language use, ability and shift. The authors examine in particular: the different ways in which languages can be mapped; how geographical insights can be used to develop understandings of language use; the value of assemblage theory as a way of interpreting the social, technical and spatial aspects of language policy development; and the geographies that characterise institutional engagements with languages. This book will set a research agenda for the geographical study of language, developing a conceptual framework that will offer fresh insights to researchers in the fields of Applied Linguistics, Sociolinguistics, Minority Languages, Geolinguistics, and Public Policy. Rhys Jones is Professor of Human Geographyat Aberystwyth University, UK Huw Lewis is Lecturer in International Politics at Aberystwyth University, UK.
Chapter 1: Introducing the geographies of languages -- Chapter 2: Charting the new the geographies of languages -- Chapter 3: Wales and the Welsh language: setting the context -- Chapter 4: The geographies of language ability -- Chapter 5: Making sense of language use -- Chapter 6: The geographies of language policy in Wales -- Chapter 7: Languages and institutional geographies -- Chapter 8: Conclusions.
Keywords: Language policy; Sociolinguistics; Human geography; Europe -- Politics and government; Political planning; Language Policy and Planning; Sociolinguistics; Human Geography; European Politics; Public Policy